Aktivitas Harian Rusa Totol (Axis Axis) di Taman Hutan Kota Muhammad Sabki Kota Jambi - Hendra Kurniawan; Thoriq DevisHoriansa; Dinda Tri Agustina; Citra Rahmatia (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Wild deer populations have declined owing to poaching and habitat loss. Conservation in captive outside deer's native environment can prevent extinction and maximize sustainable use. IUCN classifies Spotted Deer (Axis axis) as least concern. The Muhammad Sabki City Forest Park contains 5 Spotted Deer (Axis axis) from PTPN 6, 1 Male and 4 Female, presented to Jambi City Government. Captivity (ex-situ conservation) can optimize and maintain Spotted Deer use to rebuild the population. The research used Focal Animal Sampling and Continuous Recording in Muhammad Sabki City Forest Park in Jambi City in June 2024. Male and female deer were observed for data collection. Observation and computation took 10 hours with 15-minute intervals and 5 sessions.